Apakah pemberdayaan pembelajar dapat mendukung kemampuan inovatif mahasiswa? Pengujian korelasional dan komparatif - Aurelia, Fatina Zahra; Etikariena, Arum (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractCompetition between companies relies on innovations from their employees. The potential of innovative employees could be developed since they were college students. One of the many ways to see their potential is by looking at how they perceive their capabilities, impacts, and means in academic settings, also known as learner empowerment. This study aims to look at the relationship between Learner Empowerment and Innovative Work Behavior in University of Indonesia college students. Participants of this research are 539 students above freshman year, gathered using the convenience sampling technique. The instrument used are the Innovative Work Behavior Scale by Janssen (2000) (? = 0,88) and the Learner Empowerment Scale by Frymier dkk. (1996) (? = 0,87), both instruments are adapted accordingly to suit the participants for this research. Analysis techniques used are Pearson's Correlation, Independent Sample T-Test, and One-way ANOVA. Results showed that there's a positive significant relationship between learner empowerment and innovative work behaviour. Dimensions of learner empowerment (meaningfulness, competence, impact) also have significant relationships to innovative work behaviour, with impact as the strongest determinant. Further research can explore other factors that explain the relationship between these two variables.Keywords: College Students; Correlational Research; Innovative Work Behavior; Learner Empowerment AbstrakPersaingan antar perusahaan pada masa ini membutuhkan ide inovatif dari karyawannya. Kemampuan inovatif karyawan dapat dikembangkan sejak individu masih menjadi mahasiswa. Salah satunya dengan bagaimana mahasiswa mempersepsikan kemampuan, potensi, dan peran yang dimilikinya dalam lingkungan belajar, dikenal sebagai pemberdayaan pembelajar. Penelitian ini bertujuan untuk melihat hubungan antara pemberdayaan pembelajar dengan perilaku kerja inovatif pada mahasiswa Universitas Indonesia. Partisipan penelitian merupakan 539 mahasiswa yang berada di atas semester 3, didapatkan melalui teknik convenience sampling. Alat ukur yang digunakan merupakan Innovative Work Behavior Scale dari Janssen (2000) (? = 0,88) dan Learner Empowerment Scale dari Frymier dkk. (1996) (? = 0,87) yang diadaptasi menyesuaikan target partisipan penelitian. Teknik analisis yang digunakan adalah Pearson Correlation, Independent Sample T-Test, dan One-way ANOVA. Hasil penelitian menunjukkan bahwa terdapat hubungan positif dan signifikan antara Pemberdayaan Pembelajar dan Perilaku Kerja Inovatif. Ketiga dimensi pemberdayaan pembelajar (meaningfulness, competence, impact) juga secara signifikan berhubungan dengan perilaku kerja inovatif, dengan dimensi impact sebagai penentu terkuat. Penelitian lanjutan dapat mencari faktor yang mampu menjelaskan hubungan kedua variabel ini.Kata kunci: Mahasiswa; Pemberdayaan Pembelajar; Penelitian Korelasional; Perilaku Kerja Inovatif